2021
DOI: 10.1002/pon.5640
|View full text |Cite
|
Sign up to set email alerts
|

The role of attachment avoidance: A longitudinal mediation model predicting existential distress in patients with advanced cancer

Abstract: Objective Although a protective effect of reliable interpersonal relationships on existential distress has been established, evidence remains inconclusive for attachment insecurity as an underlying factor of persistent psychological distress. We tested a longitudinal model hypothesizing attachment avoidance as a mediator of high demoralization and anxiety over time. Methods We studied 206 patients with advanced cancer (mean age = 59.6, 61% female) participating in an intervention trial. Patients completed self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Third, for exploring associated factors of death anxiety, some variables may be less sensitive and representative due to convenience sampling method rather than purpose sampling method. At the same time, literature review suggested that physical symptoms, self-esteem, attachment security, 7 attachment avoidance, 68 anxiety, depression, and demoralization 14 , 58 , 68 were correlated with death anxiety. Finally, we did not involve and analyze the interaction or the intermediary role between various factors, which need to be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, for exploring associated factors of death anxiety, some variables may be less sensitive and representative due to convenience sampling method rather than purpose sampling method. At the same time, literature review suggested that physical symptoms, self-esteem, attachment security, 7 attachment avoidance, 68 anxiety, depression, and demoralization 14 , 58 , 68 were correlated with death anxiety. Finally, we did not involve and analyze the interaction or the intermediary role between various factors, which need to be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported a positive association between attachment security and demoralization, 43 one of which highlighted the positive relationship between attachment avoidance (one of the dimensions of attachment security) and demoralization. 41 In addition, social relatedness (consisting of attachment security and social support) was negatively associated with demoralization. 17 Two studies reported a positive association between death anxiety and demoralization.…”
Section: Resultsmentioning
confidence: 99%
“…17 Two studies reported a positive association between death anxiety and demoralization. 17,41 The positive relationship between suicidal ideation, 45 anger, 32 and demoralization has only been investigated in a single study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a sense of meaning in life is important for maintaining happiness and well-being in general (Cohen & Cairns, 2012; Guerrero-Torrelles et al., 2017; Melton & Schulenberg, 2008), it may be especially important for patients with cancer (Winger et al., 2020). A cancer diagnosis can, at least temporarily, leave some patients feeling demoralized, existentially distressed, and that they lack meaning and purpose in their lives (Kissane et al., 2001; Lee, 2008; Lee et al., 2004; Philipp et al., 2021; Vehling & Kissane, 2018). As many as 40% of patients with cancer in one study reported that they needed help finding meaning in life after their diagnosis (Moadel et al., 1999).…”
mentioning
confidence: 99%